PENGARUH PENGAWASAN DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI DI DINAS PENDIDIKAN KABUPATEN MUSI RAWAS - Surajiyo Surajiyo; Jepri Jepri (Jurnal Interprof, 2020)
This study aims to determine the effect of supervision and communication on the performance of Musi Rawas District Education Office employees. The method used in this study is a quantitative method, and data collection techniques used in this study are questionnaires and observations. The number of respondents 53 people. Data analysis techniques using simple regression test, correlation coefficient, t test, multiple regression test, determination test, and f test. The first hypothesis testing is the Supervision variable (X1) on employee performance (Y) which shows that the calculation produces a coefficient of 22,830. With a sample size of 53 found df = (53-2) and at a significant level of 0.05, the t-table value was 1.675. With this result it can be said that Supervision has a significant effect on Employee Performance because t arithmetic (22,830)> t table (1,675). The second hypothesis testing is the Communication variable (X2) on employee performance (Y) which shows that t arithmetic produces a coefficient of 8,178. With a sample size of 53 found df = (53-2) and at a significant level of 0.05, the t-table value was 1.675. With these results it can be said that supervision has a significant effect on employee performance because t arithmetic (8,178)> t table (1,675). Then testing the third hypothesis found that the calculated F value was 291,566> F table = 3.18 and the significant level simultaneously sig F was 0,000.